Cationic dyeable polyester and preparation method thereof

By introducing the phenyl acid -5-sulfonate and ethan glycol to the PET polymer to perform normal pressure and polymerization reactions to prepare a cationic polyester section without granular impurities, solving the PET polymer Poor dyeing performance and insufficient structural constitution have improved their applicability in fiber production.

CN114163625BActive Publication Date: 2025-01-28CHINESE TEXTILE ACAD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111394320.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-23
Publication Date
2025-01-28
Estimated Expiration
2041-11-23

AI Technical Summary

Technical Problem

The dyeing performance of existing PET polymers is poor, and technical solutions to improve the polymerization process lead to poor product structural regularity, limiting their application in fiber production.

Method used

Adopt a cationic polyester and its preparation method. By adding the esterization reactions of phenyl acidic acid and dilate, the phenyl-5-sulfonate and ethylene glycolic alcohol and ethylene glycol are added to the ester. , Perform normally pressure reactions and clustering reactions to obtain cationic polyester slices with impurities without particulate matter.

Benefits of technology

This method reduces the generation of side effects. The cationic ions can be dyed polyester without particulate impurities, which is suitable for spinning processing, which enhances its application potential in fiber production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003369405160000101
    Figure BDA0003369405160000101
  • Figure BDA0003369405160000111
    Figure BDA0003369405160000111
Patent Text Reader

Abstract

The present invention provides a cationic dyeable polyester and a preparation method thereof, belonging to the technical field of polymer materials. The cationic dyeable polyester has no particulate impurities, is conducive to subsequent spinning processing, and has important significance for the expansion and application of the cationic dyeable polyester. The preparation method of the cationic dyeable polyester can prepare the cationic dyeable polyester. First, terephthalic acid and diol are mixed in a molar ratio of 1: (1.2-1.4) and then esterified to obtain an esterified product; then, an esterified product of isophthalic acid-5-sulfonate and ethylene glycol is added to the esterified product, and a normal pressure reaction is carried out to obtain an intermediate product; finally, the intermediate product is sequentially subjected to polycondensation reaction, cooling, and pelletizing to obtain the cationic dyeable polyester slice provided by the present invention, which avoids the generation of side reactions when the mixture of isophthalic acid-5-sulfonate and ethylene glycol is directly used for addition and use, so that the prepared cationic dyeable polyester has no particulate impurities, which is conducive to the normal progress of subsequent spinning processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a cationic dyeable polyester and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET), also known as polyester resin, is a condensation product of terephthalic acid and ethylene glycol. Conventional PET has a dense structure and no dyeing groups, resulting in poor dyeing performance. It can only be dyed with disperse dyes under high temperature and high pressure conditions. The technical solutions for improving the PET polymerization process in the prior art have poor structural regularity of the product, which limits its application in fiber production. Summary of the invention

[0003] In view of this, the present invention provides a cationic dyeable polyester and a preparation method thereof. The cationic dyeable polyester prepared by the preparation method has few side reactions in the process, and the prepared cationic dyeable polyester has no particulate impurities, which is conducive to spinning processing and is more suitable for practical use.

[0004] In order to achieve the above first object, the technical scheme of cationic dyeable polyester provided by the present invention is as follows:

[0005] The cationic dyeable polyester provided by the invention contains no particulate impurities.

[0006] The cationic dyeable polyester provided by the present invention can also be further realized by adopting the following technical measures.

[0007] Preferably, the cationic dyeable polyester slices are dissolved in a phenol-tetrachloroethane solution with a mass ratio of 1:1, the mass percentage of the cationic dyeable polyester is 1%, the test temperature is 25° C., and the intrinsic viscosity ranges from 0.50 dL / g to 0.62 dL / g.

[0008] In order to achieve the above second purpose, the technical scheme of the preparation method of cationic dyeable polyester provided by the present invention is as follows:

[0009] The preparation method of the cationic dyeable polyester provided by the present invention comprises the following steps:

[0010] Terephthalic acid and diol are mixed in a molar ratio of 1:(1.2-1.4) and then subjected to an esterification reaction to obtain an esterification product, wherein the esterification rate of the esterification product is ≥90%;

[0011] Adding an ester of 5-sulfonate of isophthalic acid and ethylene glycol to the esterification product, and reacting at normal pressure to obtain an intermediate product, wherein the esterification rate of the ester of 5-sulfonate of isophthalic acid and ethylene glycol is in the range of 75% to 85%, and the amount of the ester of 5-sulfonate of isophthalic acid and ethylene glycol added is 1.5% to 3.0% of the amount of the terephthalic acid substance;

[0012] The intermediate product is sequentially subjected to polycondensation reaction, cooling, and pelletizing to obtain the cationic dyeable polyester chips.

[0013] The method for preparing the cationic dyeable polyester provided by the present invention can also be further implemented by adopting the following technical measures.

[0014] Preferably, in the step of mixing terephthalic acid and diol in a molar ratio of 1:(1.2-1.4) and then subjecting them to an esterification reaction to obtain an esterification product, a step of adding a catalyst is also included, wherein the catalyst is selected from one or a mixture of antimony trioxide, antimony glycol, antimony acetate, calcium acetate, zinc acetate, sodium acetate, tetrabutyl titanate, tetraisopropyl titanate, and tetraisooctyl titanate, and the amount of the catalyst added is 0.01%-0.06% of the weight of the copolyester.

[0015] Preferably, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol or a mixture thereof.

[0016] Preferably, the 5-sulfonate of isophthalic acid comprises at least one of 5-sulfonate sodium isophthalate or 5-sulfonate potassium isophthalate or a mixture thereof.

[0017] Preferably, in the step of mixing terephthalic acid and diol in a molar ratio of 1:(1.2-1.4) and then subjecting them to an esterification reaction to obtain an esterified product, the temperature of the esterification reaction ranges from 240°C to 265°C.

[0018] Preferably, in the step of mixing terephthalic acid and diol in a molar ratio of 1:(1.2-1.4) and then subjecting them to an esterification reaction to obtain an esterification product, a step of adding a stabilizer is also included, wherein the stabilizer is selected from one or a mixture of triphenyl phosphite, trimethyl phosphate, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate, tris(2,4-di-tert-butylbenzene) phosphite, and 3,5-bis(1,1-dimethylethyl)-4-hydroxy-phenylpropionate-1,6-hexanediyl ester, and the amount of the stabilizer added is 0.005%-0.05% by weight of the copolyester.

[0019] Preferably, the step of obtaining the cationic dyeable polyester chips by polycondensation of the intermediate product comprises a pre-polycondensation reaction stage and a final polycondensation reaction stage, wherein:

[0020] The control temperature of the pre-polycondensation reaction stage is in the range of 250°C-275°C, and the pressure is in the range of 1kPa-4kPa;

[0021] The control temperature of the final polycondensation reaction stage is in the range of 260° C.-285° C., and the pressure is in the range of 0.005 kPa-0.5 kPa.

[0022] Preferably, in the step of adding the esterification product of isophthalic acid-5-sulfonate and ethylene glycol to the esterification product to carry out normal pressure reaction to obtain the intermediate product, the duration of the normal pressure reaction ranges from 30 min to 60 min.

[0023] Preferably, in the steps of sequentially subjecting the intermediate product to polycondensation reaction, cooling, and pelletizing to obtain the cationic dyeable polyester chips, the polycondensation reaction is terminated when the viscosity of the copolyester is in the range of 0.50 dL / g-0.62 dL / g.

[0024] The cationic dyeable polyester provided by the present invention contains no particulate impurities, is beneficial to subsequent spinning processing, and has important significance for the expanded application of the cationic dyeable polyester.

[0025] The preparation method of the cationic dyeable polyester provided by the present invention can prepare the cationic dyeable polyester provided by the present invention. First, terephthalic acid and diol are mixed in a molar ratio of 1:(1.2-1.4) and then subjected to an esterification reaction to obtain an esterification product; then, an esterification product of isophthalic acid-5-sulfonate and ethylene glycol is added to the esterification product to carry out a normal pressure reaction to obtain an intermediate product; finally, the intermediate product is subjected to a polycondensation reaction, cooling, and pelletizing in sequence to obtain the cationic dyeable polyester slice provided by the present invention, which avoids the generation of side reactions when a mixture of isophthalic acid-5-sulfonate and ethylene glycol is directly used for addition and use, so that the prepared cationic dyeable polyester has no particulate impurities, which is conducive to the normal progress of subsequent spinning processing. DETAILED DESCRIPTION

[0026] In view of this, the present invention provides a cationic dyeable polyester and a preparation method thereof. The cationic dyeable polyester prepared by the preparation method has few side reactions in the process, and the prepared cationic dyeable polyester has no particulate impurities, which is conducive to spinning processing and is more suitable for practical use.

[0027] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a cationic dyeable polyester and its preparation method according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, the specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.

[0028] The term "and / or" in this article is merely a description of the association relationship of associated objects, indicating that three relationships may exist, for example, A and / or B. Specifically, it is understood that: A and B may be included at the same time, A may exist alone, or B may exist alone, and any of the above three situations may be met.

[0029] The inventor has found through arduous efforts that in the process of producing polyester dyeable with cationic dyes, diethylene glycol isophthalate-5-sulfonate is often used as a copolymer monomer, and the preparation of the monomer is all prepared with diethylene glycol isophthalate-5-sulfonate as a raw material. The route is long, and the prepared diethylene glycol isophthalate-5-sulfonate exists in the form of 20%-40% ethylene glycol solution or mixed solution, which will produce monomer precipitation during storage, which is not conducive to storage, transportation and product quality stability. In order to solve the above problems, diethylene glycol isophthalate-5-sulfonate is directly used to mix with ethylene glycol and added to the polyester reaction system, which can effectively shorten the preparation process of the raw materials and reduce the cost. However, when diethylene glycol is directly used to mix and add with ethylene glycol, due to the generation of side reactions, obvious particulate matter will be produced in the polymer, thereby affecting the normal spinning process, thereby affecting the promotion and use of the route.

[0030] Example 1

[0031] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.4, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is antimony trioxide and zinc acetate, and the added amount of the catalyst is 0.06% of the weight of the copolyester. The stabilizer is triphenyl phosphite, and the added amount of the stabilizer is 0.05% of the weight of the copolyester. The temperature of the esterification reaction is 245°C. When the esterification rate reaches 90%, the esterification reaction is completed.

[0032] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 75% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 60 minutes;

[0033] Then the temperature was raised to 255°C for pre-polycondensation reaction at a pressure of 1 kPa. After the pre-polycondensation reaction, the temperature was raised to 285°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.58 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0034] Example 2

[0035] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.2, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is ethylene glycol antimony, and the added amount of the catalyst is 0.06% by weight of the copolyester. The stabilizer is trimethyl phosphate, and the added amount of the stabilizer is 0.005% by weight of the copolyester. The temperature of the esterification reaction is 265°C. When the esterification rate reaches 92%, the esterification reaction is completed.

[0036] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 80% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 30 minutes;

[0037] Then the temperature was raised to 275°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.56 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0038] Example 3

[0039] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.3, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is antimony trioxide and antimony acetate, and the added amount of the catalyst is 0.06% of the weight of the copolyester. The stabilizer is pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxy) benzene propionate, and the added amount of the stabilizer is 0.005% of the weight of the copolyester. The temperature of the esterification reaction is 250°C. When the esterification rate reaches 95%, the esterification reaction is completed.

[0040] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 85% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 30 minutes;

[0041] Then the temperature was raised to 260°C for pre-polycondensation reaction at a pressure of 4 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.59 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0042] Example 4

[0043] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.4, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is antimony trioxide and calcium acetate, and the amount of the catalyst added is 0.06% of the weight of the copolyester. The stabilizer is tri(2,4-di-tert-butylbenzene) phosphite, and the amount of the catalyst added is 0.005% of the weight of the copolyester. The temperature of the esterification reaction is 250°C. When the esterification rate reaches 97%, the esterification reaction is completed.

[0044] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 85% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 3.0% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 30 minutes;

[0045] Then the temperature was raised to 270°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.50 dL / g, the copolyester chips were obtained after cooling and pelletizing.

[0046] Example 5

[0047] Terephthalic acid and 1,3-propylene glycol in a molar ratio of 1:1.4, as well as a catalyst and a stabilizer are mixed and added into an esterification reactor for esterification reaction. The catalyst is tetrabutyl titanate and sodium acetate, and the amount of the catalyst added is 0.01% of the weight of the copolyester. The stabilizer is 3,5-di(1,1-dimethylethyl)-4-hydroxy-phenylpropionic acid-1,6-hexanediyl ester, and the amount of the stabilizer added is 0.01% of the weight of the copolyester. The temperature of the esterification reaction is 250°C. When the esterification rate reaches 97%, the esterification reaction ends.

[0048] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 85% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 60 minutes;

[0049] Then the temperature was raised to 255°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 265°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.61 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0050] Example 6

[0051] Terephthalic acid and 1,4-butanediol in a molar ratio of 1:1.4, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is tetrabutyl titanate and sodium acetate, and the added amount of the catalyst is 0.01% of the weight of the copolyester. The stabilizer is pentaerythritol tetra(3,5-di-tert-butyl-4-hydroxy)phenylpropionate, and the added amount of the stabilizer is 0.01% of the weight of the copolyester. The temperature of the esterification reaction is 240°C. When the esterification rate reaches 97%, the esterification reaction is completed.

[0052] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 85% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 60 minutes;

[0053] Then the temperature was raised to 250°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 260°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.60 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0054] Example 7

[0055] Terephthalic acid and 1,4-butanediol in a molar ratio of 1:1.4, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is tetrabutyl titanate and sodium acetate, and the added amount of the catalyst is 0.01% of the weight of the copolyester. The stabilizer is pentaerythritol tetra(3,5-di-tert-butyl-4-hydroxy)phenylpropionate, and the added amount of the stabilizer is 0.01% of the weight of the copolyester. The temperature of the esterification reaction is 240°C. When the esterification rate reaches 97%, the esterification reaction is completed.

[0056] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 85% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 60 minutes;

[0057] Then the temperature was raised to 250°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 265°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.62 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0058] Example 8

[0059] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.3, as well as a catalyst and a stabilizer are mixed and added into an esterification reactor for esterification reaction. The catalyst is antimony trioxide and antimony acetate, and the amount of the catalyst added is 0.06% of the weight of the copolyester. The stabilizer is pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxy) benzene propionate, and the amount of the stabilizer added is 0.01% of the weight of the copolyester. The temperature of the esterification reaction is 250°C. When the esterification rate reaches 95%, the esterification reaction ends.

[0060] Add a mixture of potassium 5-sulfonate of isophthalic acid and ethylene glycol with an esterification rate of 82% to the reaction system, and the amount of potassium 5-sulfonate of isophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 30 minutes;

[0061] Then the temperature was raised to 265°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.58 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0062] Comparative Example 1

[0063] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.3, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is antimony trioxide, and the amount of the catalyst added is 0.06% by weight of the copolyester. The stabilizer is triphenyl phosphite, and the amount of the stabilizer added is 0.01% by weight of the copolyester. The temperature of the esterification reaction is 250°C. When the esterification rate reaches 90%, the esterification reaction ends.

[0064] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 0% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 30 minutes;

[0065] Then the temperature was raised to 260°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.57 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0066] Comparative Example 2

[0067] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.3, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is ethylene glycol antimony, and the added amount of the catalyst is 0.06% by weight of the copolyester. The stabilizer is triphenyl phosphite, and the added amount of the stabilizer is 0.01% by weight of the copolyester. The temperature of the esterification reaction is 255°C. When the esterification rate reaches 95%, the esterification reaction is completed.

[0068] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 50% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 1.5% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 60 minutes;

[0069] Then the temperature was raised to 260°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.59 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0070] Comparative Example 3

[0071] Terephthalic acid and ethylene glycol in a molar ratio of 1:1.3, as well as a catalyst and a stabilizer are mixed and added to an esterification reactor for esterification reaction. The catalyst is ethylene glycol antimony, and the added amount of the catalyst is 0.06% by weight of the copolyester. The stabilizer is triphenyl phosphite, and the added amount of the stabilizer is 0.01% by weight of the copolyester. The temperature of the esterification reaction is 255°C. When the esterification rate reaches 95%, the esterification reaction is completed.

[0072] Add a mixture of 5-sodium sulfoisophthalic acid and ethylene glycol with an esterification rate of 50% to the reaction system, and the amount of 5-sodium sulfoisophthalic acid added is 3.0% of the amount of terephthalic acid in the system. After mixing evenly, continue the reaction at normal pressure for 60 minutes;

[0073] Then the temperature was raised to 260°C for pre-polycondensation reaction at a pressure of 2 kPa. After the pre-polycondensation reaction, the temperature was raised to 280°C for final polycondensation reaction at a pressure of 0.1 kPa. When the viscosity of the copolyester reached 0.51 dL / g, the reaction was terminated, and the copolyester chips were obtained after cooling and pelletizing.

[0074] The comparison of the slices of Examples 1-8 and Comparative Examples 1-3 is shown in Table 1 below:

[0075] Table 1

[0076]

[0077]

[0078] As can be seen from the above table, in Comparative Examples 1-3, the esterification rate of the sulfonate monomer used is 0-50%, and the slices prepared by adding the sulfonate monomer to the reaction system have more particulate impurities, which will clog the spinneret assembly during the spinning process, which is not conducive to the back-end spinning application processing. In Examples 1-8, the esterification rate of the sulfonate monomer used is 75%-85%, and the slices prepared by adding the sulfonate monomer to the reaction system have no particulate impurities, which can meet the requirements of stable spinning and is conducive to spinning application processing.

[0079] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0080] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a cationic dyeable polyester, characterized in that: The preparation method of the cationic dyeable polyester comprises the following steps: Terephthalic acid and diol are mixed in a molar ratio of 1:(1.2-1.4) and then subjected to an esterification reaction to obtain an esterification product, wherein the esterification rate of the esterification product is ≥90%; Adding an ester of 5-sulfonate of isophthalic acid and ethylene glycol to the esterification product, and reacting at normal pressure to obtain an intermediate product, wherein the esterification rate of the ester of 5-sulfonate of isophthalic acid and ethylene glycol is in the range of 75% to 85%, and the amount of the ester of 5-sulfonate of isophthalic acid and ethylene glycol added is 1.5% to 3.0% of the amount of the terephthalic acid substance; The intermediate product is sequentially subjected to polycondensation reaction, cooling, and pelletizing to obtain the cationic dyeable polyester chips, wherein no side reaction occurs between the isophthalic acid-5-sulfonate and ethylene glycol, so that the obtained cationic dyeable polyester contains no particulate impurities.

2. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The step of mixing terephthalic acid and diol in a molar ratio of 1:(1.2-1.4) and then subjecting them to an esterification reaction to obtain an esterification product also includes the step of adding a catalyst, wherein the catalyst is selected from one or a mixture of antimony trioxide, antimony glycol, antimony acetate, calcium acetate, zinc acetate, sodium acetate, tetrabutyl titanate, tetraisopropyl titanate, and tetraisooctyl titanate, and the amount of the catalyst added is 0.01%-0.06% of the weight of the copolyester.

3. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol or a mixture thereof.

4. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The 5-sulfonate of isophthalic acid includes at least one of sodium 5-sulfonate of isophthalic acid or potassium 5-sulfonate of isophthalic acid, or a mixture thereof.

5. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The terephthalic acid and the diol are mixed in a molar ratio of 1:(1.2-1.4) and then subjected to an esterification reaction to obtain an esterified product. The temperature of the esterification reaction ranges from 240°C to 265°C.

6. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The step of mixing terephthalic acid and diol in a molar ratio of 1:(1.2-1.4) and then subjecting them to an esterification reaction to obtain an esterified product also includes the step of adding a stabilizer, wherein the stabilizer is selected from one of triphenyl phosphite, trimethyl phosphate, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate, tris(2,4-di-tert-butylbenzene) phosphite, and 3,5-bis(1,1-dimethylethyl)-4-hydroxy-phenylpropionate-1,6-hexanediyl ester, or a mixture of several thereof, and the added amount of the stabilizer is 0.005%-0.05% of the weight of the copolyester.

7. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The step of obtaining the cationic dyeable polyester chips by polycondensation of the intermediate product includes a pre-polycondensation reaction stage and a final polycondensation reaction stage, wherein: The control temperature of the pre-polycondensation reaction stage is in the range of 250°C-275°C, and the pressure is in the range of 1kPa-4kPa; The control temperature of the final polycondensation reaction stage is in the range of 260° C.-285° C., and the pressure is in the range of 0.005 kPa-0.5 kPa.

8. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: In the step of adding the esterification product of isophthalic acid-5-sulfonate and ethylene glycol to the esterification product and reacting at normal pressure to obtain the intermediate product, the duration of the normal pressure reaction ranges from 30 min to 60 min.

9. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The intermediate product is sequentially subjected to polycondensation reaction, cooling, and pelletizing to obtain the cationic dyeable polyester chips. The polycondensation reaction is terminated when the viscosity of the copolyester is in the range of 0.50 dL / g-0.62 dL / g.

10. The method for preparing a cationic dyeable polyester according to claim 1, characterized in that: The cationic dyeable polyester slices are dissolved in a phenol-tetrachloroethane solution with a mass ratio of 1:1, the mass percentage of the cationic dyeable polyester is 1%, and the test temperature is 25° C. The intrinsic viscosity ranges from 0.50 dL / g to 0.62 dL / g.

Citation Information

Patent Citations

  • Preparation method for anti-pilling, anti-ageing and normal-pressure cation dyeable polyester chips

    CN102391487A

  • Preparation method for copolyester containing sodium sulfonate group

    CN110938197A

  • Preparation method of moisture-absorbing and sweat-releasing ECDP fiber

    CN111304781A